USE OF CABRI 3D V2 SOFTWARE INCREASE STUDENT MATHEMATICAL ACTIVITIES AND LEARNING OUTCOMES IN MATERIAL THREE DIMENSIONS - Safiil Maarif; Meydi Widya Pangestika (Jurnal Prinsip Pendidikan Matematika, 2021)
Based on the results of observations of the daily test scores of class XII Science 1 MAN 1 Mojokerto City on the three dimensional material as much as 5 students the grades have met the KKM (Minimum completeness criteria) while the other 25 students have not met the KKM, with an average grade of 58 and learning outcomes classical reached 16.67%. The low student learning outcomes because students do not understand how to visualize the shape of the three dimensions and the understanding of the concept of distance in the third dimension that is lacking. Monotonous student learning activities make students tend to talk alone when the teacher explains the material. The application of Cabri 3D V2 software will help students visualize three-dimensional shapes and understand the material easily. This study aims to describe the increase in student activity and learning outcomes in participating in learning using Cabri 3D V2 software. This type of research is Classroom Action Research (CAR) using two cycles. One cycle consists of four stages, namely planning, action, observation, and reflection. Data collection methods used are observation and test methods. Instrument validation is carried out by expert validates. The research subjects were students of class XII Science 1 MAN 1 Mojokerto, which consisted of 30 students. Based on the results of research in cycles I and II seen an increase in student activity in cycle I by 63% with criteria C (Enough) in cycle II to 85% with criteria B (Good). Mastery learning outcomes of students in cycle I was 47% with an average of 71.97 and cycle II was 89% with an average of 89.96. In cycle II has reached the criteria of success, namely student activity and learning outcomes have reached = 76% classically then by applying Cabri 3D V2 software can increase student activity and learning outcomes